Tres poemas mágicos - Luján, Jorge 1943- (Anaya, 2007)
Three poems about a witch whose drawings come to life, a ghost who gets lost at night and is invisible during the day, and an angel who can't find his wings
Garabato -- Señales -- Sed de Ángel
Keywords: Witches / Juvenile poetry; Angels / Juvenile poetry; Ghosts / Juvenile poetry; Children's poetry, Spanish; Angels; Ghosts; Witches; Bilderbuch